Conflicts of Interest in "Throwaway" Dermatology Publications: Analysis of the Open Payments Database - Jorge Roman; David J Elpern (JMIR Publications, 2021)
BackgroundDermatology journals, periodicals, editorials, and news magazines are influential resources that are not uniformly regulated and subject to influence from the pharmaceutical industry. This study evaluates industry payments to physician editorial board members of common dermatology publications, including "throwaway" publications. ObjectiveThe aim of this study was to characterize the extent and nature of industry payments to editorial board members of different dermatologic publications in order to ascertain differences in payments between different types of publications. MethodsA list of editorial board members was compiled from a collection of clinical dermatology publications received over a 3-month period. Data from the Open Payments database from 2013 to 2019 were collected, and analysis of payments data was performed. ResultsTen publications were evaluated, and payments data for 466 physicians were analyzed. The total compensation across all years was US $75,622,369.64. Consulting, services other than consulting, and travel or lodging payments constituted most of the payments. A fraction of dermatologists received the majority of payments. The top payers were manufacturers of biologic medications. Payment amounts were higher for throwaway publications compared to peer-reviewed journals. ConclusionsEditorial board members of dermatology publications received substantial payments from the pharmaceutical industry. A minority of physicians receive the lion's share of payments from industry. "Throwaway" publications have more financial conflict of interest than do peer-reviewed journals. The impact of these conflicts of interest on patient care, physicians' practice patterns, and patient perception of physicians is noteworthy.